GAMBARAN PERLAKUAN MOBILISASI DINI TERHADAP INVOLUTIO UTERI PADA POST SECTIO CAESAREA DI RUMAH SAKIT UMUM KAB TANGERANG TAHUN 2016 - Suyatini Suyatini; endang suartini (Politeknik Kesehatan Kementerian Kesehatan Banten, 2020)
Background This study is still high Postpartum mothers through Sectio Caesarea at Tangerang District General Hospital 2016 (65.9%) and the implementation of early mobilization by 67% and not mobilization (33%) as a problem is whether early mobilization has an influence on the involution uterine postpartum mothers with Sectio Caesarea research objective is to obtain an information depiction of early mobilization against involution uterus, results penelitian can be inmanfaatright by hospitals and other researchers design study a descriptive to look at the picture of early mobilization terhadap involution of the uterus research performed in Tangerang District Public Hospital in September to November 2016 population of this study was Postpartum mothers with Sectio Caesarea in Tangerang District General Hospital, while samples were taken using Non Probability Sampling (Non Random) using Accidental Sampling with inclusion criteria Postpartum mothers with Sectio Caesarea who were treated for at least 3 days and maternal exclusion criteria Postpartum suffering from Chronic disease, data were collected using observation sheets, data were processed and analyzed by Univariate and Bivariate. results Early Showed Mobilization have an impact on involution uteri, discussion connect with expert opinion and factors physiological reproductive and opinions of researchers, the advice given to the hospital and midwife in the inpatient unit. Keywords: Early Mobilization, Uterine Involution, Pre and Post, Average, Caesarean Section